Pengaruh Pembelajaran Berbasis Joyful Learning Terhadap Pembelajaran Mendalam Pada Anak Usia Dini - Putri Kharisma Dewi; Een Yayah Haenilah; Nopiana Nopiana (Jambura Early Childhood Education Journal, 2026)
This study was motivated by the low level of deep learning among early childhood students, as evidenced by a lack of active engagement, critical thinking skills, and difficulties in connecting learning experiences to daily life. This study aims to determine the effect of joyful learning-based instruction on deep learning in early childhood. The research hypothesis is that there is an effect of joyful learning-based instruction on deep learning in early childhood. The study employed a quantitative approach using a pre-experimental design with a one-group pretest-posttest design. The study subjects consisted of 23 children aged 5–6 years at Al-Akbar Rajabasa Kindergarten in Bandar Lampung. Data were collected through observation and analyzed using the Wilcoxon test. The results showed an Asymp. Sig. (2-tailed) value of 0.000 < 0.05, indicating that joyful learning-based instruction has an effect on deep learning in young children. Learning activities through play, experiments, projects, and concrete media encourage children to be more active, understand concepts, and reflect on their learning experiences. The research findings suggest that deep learning in early childhood should take place in an integrated manner to optimally stimulate the development of young children.